(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Law enforcement agencies hold a vital job in the productive running of the nation. They keep up law and request in a nation and guarantees that harmony and valor wins in the nation. A country’s satisfaction can be assessed from multiple points of view. Mental security of person’s is one of the ways. A country where the general population are constantly frightful of occurring of some obscure occasion can’t be said to be a glad country. ’Being secure’ is the first need of any person so as to have an upbeat existence. Law enforcement agencies make us secure, which is their most extreme duty. The CBI has as of late been unmistakably in the news, accepting bunches from a few and brickbats from others. The Indian culture has been having a type of an adoration detest association with this association. The CBI has regularly been censured for its supposed inability to work unbiasedly and dispassionately as an agency of law, yet all the while there has dependably been a consistently expanding demand for examination of muddled cases including compelling people to be handed over to the CBI. This occurs in spite of the fact that the record of CBI in such cases has not been truly laudable.